Differences in the orientation towards helping others among university students in light of the gender variable: a comparative study - MHAMEL, Imad Eddine (Journal of Human Sciences, 2025)
The study investigated the differences in the orientation towards helping others among university students in Algeria, focusing on gender as a variable. Utilizing a descriptive method and a scale developed by Shaaban and Al-Shawareb, the researcher analyzed responses from 205 students during the first semester of the 2024-2025 academic year which was determined by the facilitated method The findings revealed that the Algerian university students in the study sample have a high level of orientation towards helping others, where the dimension of empathy came first, followed by the dimension of helping in life situations and then after helping in situations of danger while no significant gender differences were found in their helping orientation.